Nations in Review(s): Modernist “Little” Magazines and the (Trans)National Imagination - Canelo, Maria José (2018)
This article brings together three case-studies of modernist “little” magazines: Orpheu (1915) and Portugal Futurista (1917), in Portugal; Klaxon (1922–1923) and Revista de Antropofagia (1928–1929), in Brazil, and The Seven Arts (1916–1917), in the United States. The article proposes a comparative analysis of texts published in the magazines with a view to shed light on their contribution to debates on nation building. Besides considering the role of “little” magazines as heralds of new controversial ideas and as springboards for new artists, the essay examines the magazines as microcosms of the cultural and social models under revision in modernist theories and aesthetics. The magazines are ultimately taken as imagined communities that aimed at redefining the borders of the nation and the meanings of national identity by means of new interpretations both of national culture and of the role poets and intellectuals played in it.